Why are Saving Rates of Urban Households in China Rising? - Chamon, Marcos (IMF Working Papers; Working Paper ;, 2008)
From 1995 to 2005, the average urban household saving rate in China rose by 7 percentage points, to u of disposable income. We use household-level data to explain the postponing of consumption despite rapid income growth. Tracing cohorts over time indicates virtually no consumption smoothing over the life cycle. Saving rates have increased across all demographic groups, although the age-profile of savings has an unusual U-shaped pattern, with saving rates being the highest among the youngest and oldest households in recent years. These patterns are best explained by the rising private burden of expenditures on housing, education, and health care.